UHPLC-LTQ OrbiTrap MS analysis and biological properties of Origanum vulgare subsp. viridulum obtained by different extraction methods - ŞENKARDEŞ, İSMAİL (ELSEVIER, 2020)
The growing awareness on implications related to the use of harsh chemicals and non-sustainable extraction methods of bioactive compounds from plants is causing a paradigm shift towards a more eco-friendly approach. The present study sets out to investigate the possible variation in the antioxidant, mutagenic/antimutagenic, antimicrobial, and enzyme inhibitory properties of Origanum vulgare subsp. viridulum extracts obtained using conventional, namely, maceration and Soxhlet extraction, and non-conventional, namely, ultrasound-assisted (UAE), microwave-assisted (MAE), and accelerated solvent extraction (ASE), techniques. Also, chemical characterization of these extracts were performed via ultrahigh-performance liquid chromatography and mass spectrometry (UHPLC-LTQ OrbiTrap MS) technique. A total of 58 polyphenols were identified in the tested extracts. Highest phenolic content was obtained from ASE (186.63 mg gallic acid equivalent [GAE]/g) and MAE (170.90 mg GAE/g) extracts. Maceration extract (18.89 mg rutin equivalent [RE]/g) showed highest flavonoid content. ASE extract showed highest activity in the DPPH (359.45 mg Trolox equivalent [TE]/g), ABTS (679.63 mg TE/g), FRAP (1433.94 mg TE/g), and CUPRAC (1685.72 mg TE/g) assays. In terms of enzyme inhibition, the UAE extract showed highest activity against acetyl cholinesterase (4.55 mg galantamine equivalent [GALAE]/g), butyryl cholinesterase (6.12 mg GALAE/g), and tyrosinase (173.87 mg kojic acid equivalent [KAE]/g) compared with the other extracts. The extracts exhibited significant antimutagenic and antimicrobial properties. Data collected from this study support the use of ASE and UAE in the extraction of bioactive compounds from Origanum vulgare subsp. viridulum aerial parts.
Keywords: Origanum; Chemical profile; Extraction; Mutagenity; Antimicrobial; MASS-SPECTROMETRY; ROSMARINIC ACID; ESSENTIAL OIL; ANTIPROLIFERATIVE ACTIVITY; ASPHODELINE-ANATOLICA; CHEMICAL-CONSTITUENTS; MEDICINAL-PLANTS; MENTHA-PULEGIUM; ONITES L.; ANTIOXIDANT